KERUKUNAN DAN TOLERANSI ANTAR UMAT BERAGAMA DALAM MEWUJUDKAN KESEJAHTERAAN SOSIAL - Derry Ahmad Rizal; Ahmad Kharis (Prodi Pengembangan Masyarakat Islam Fakultas Dakwah dan Ilmu Komunikasi UIN Mataram, 2022)
Diversity such as culture, ethnicity, race, religion and belief in Indonesia this value must be present in the community. This value of tolerance and harmony is the basis in this study, as well as with data from the Tolerant Cities Index published by SETARA Institute the city of Salatiga ranks first in the city that has the highest tolerance with a point of 6,617. More deep harmony and tolerance among religious people takes sampling of several small families with multi-religious lives. In order to achieve harmony and tolerance to mean well-being, it is necessary to build strong and good communication interactions. The other side of this good communication includes respect in worship and not considering choosing even with the assumption that one religion becomes the majority religion.